ETHICS IN FOCUS: A BIBLIOMETRIC AND CONTENT ANALYSIS OF ISLAMIC BANKING AND FINANCE RESEARCH - Zahari, Siti Aisyah; Shahimi, Shahida; Alma’amun, Suhaili; Ismail, Abdul Ghafar (Journal of Islamic Monetary Economics and Finance, 2024)
This study performs a bibliometric analysis of the literature on ethics in Islamic banking and finance (IBF) in the Scopus database. A total of 366 scholarly articles pertaining to the subject of ethics in IBF are analyzed using VOSviewer, Wordstats, Harzing’s Publish or Perish and Microsoft Excel. The development of the literature on ethics in IBF is outlined in this study, along with a list of the most significant authors, as well as relevant nations, groups, and journal sources. Moreover, the study identifies six major clusters namely, corporate image and customer loyalty of IBF, ethical decision making in IBF, Islamic work ethics, IBF standards and supervisory, ethical products and services of IBF, and maqasid al-shariah and IBF. The findings show an increasing number of citations and documents related to ethics in IBF whereby, the journal of "International Journal of Islamic and Middle Eastern Finance and Management" makes a substantial contribution to the field of ethics in IBF, both in terms of number of articles published and citation counts. The study offers the opportunity for future research to focus on these topics. Acknowledgment This paper is part of the research funded by the Faculty of Economics and Management, Universiti Kebangsaan Malaysia under Geran Inisiatif Penyelidikan (EP-2023-016) entitled "The Policy Framework of Ethical Banking for Malaysian Financial Institutions". We would also like to express our gratitude to the participants and discussants of The 9th International Islamic Monetary Economics and Finance Conference (9th IIMEFC), held on 25th October 2023, who provided valuable insights that significantly contributed to the improvement of the paper.